The Role of Employer Branding in Attracting Top Talent in the Industry 5.0 Era - Vivia Maya Rafica; Nur Elif (Jurnal Manajemen dan Profesional, 2026)
The rapid transformation of the business world under Industry 5.0 is pushing companies toward more responsive, value-based human resource management. Employer branding, the strategy organizations use to build a positive image as an ideal workplace, is gaining increasing attention as a way to attract and retain top talent. This paper explores its role in attracting Millennials and Gen Z, strengthening employee loyalty, and building competitive advantage, based on a qualitative-descriptive review of primary literature from the last seven years. The results show that successful employer branding emphasizes the Employee Value Proposition (EVP), integrates digital technology and social media, and prioritizes values such as sustainability and work-life balance, while also identifying strategic challenges and managerial implications for the Industry 5.0 era.